Effect of positive carbon-11-choline PET/CT results in the therapeutic management of prostate cancer biochemical relapse. Issue 1 (January 2019) - Gómez-de la Fuente, Francisco J.; Martínez-Rodríguez, Isabel; De Arcocha-Torres, Maria; Quirce, Remedios; Jiménez-Bonilla, Julio; Martínez-Amador, Néstor; Sánchez-Salmón, Aida; Lucas-Velázquez, Blanca; Cuenca-Vera, Oriana; Banzo, Ignacio
Abstract : Objective: Carbon-11-( 11 C)-choline PET/computed tomography (CT) has shown good results in re-staging of prostate cancer (PCa) with raised serum levels of prostate-specific antigen. Our aim was to evaluate the effect of positive 11 C-choline PET/CT results in the therapeutic management of patients with PCa with biochemical relapse (BR) after curative intention treatment. Patients and methods: A total of 112 patients with PCa BR and positive 11 C-choline PET/CT were retrospectively evaluated. PET/CT was acquired 20 min after intravenous administration of 555–740 MBq of 11 C-choline. The therapeutic management after 11 C-choline PET/CT was obtained from the clinical records. The minimum follow-up time was 18 months. Results: In 80 (71.4%) of 112 patients, 11 C-choline PET/CT showed local recurrence of PCa; in 17 (15.2%) patients, distant recurrence; and in 15 (13.4%) patients, local plus distant recurrence. A second malignancy was detected in five (4.5%) patients. The planned therapeutic management was changed as per positive 11 C-choline PET/CT result in 74 (66.1%) patients and were treated as follows: 31 (27.7%) patients with HT, combined with other treatments in eight (7.1%), 17 (15.2%) with BT, 13 (11.6%) with external beam radiotherapy, one (0.9%) with RP, and four (3.6%) with chemotherapy. Treatment approach was not modified in 37 (33%) patients. No data was available from one (0.9%) patient. Conclusion: Positive 11 C-choline PET/CT result had an important effect in the therapeutic management of patients with PCa and BR, leading to a change in the planned approach in two (66.1%) out of three patients. In addition, in 4.5% of the patients, the 11 C-choline PET/CT allowed the detection of a second malignancy.